Voluntarism, values and community : an intersubjective reading of Bas C. van Fraassen's The empirical stance - Braae, Elizabeth (Department of Philosophy, 2015)
In The Empirical Stance, Bas C. van Fraassen suggests that philosophical positions include non-factual things like values and attitudes: they are "stances" rather than factual theses. Choosing between stances is not a matter of reason or rational compulsion; rather, we choose the stance that best reflects or expresses our values. For Dien Ho and Anja Jauernig, however, this reduces philosophy to a subjective expression of personal preference (subjectivism) and, moreover, reduces philosophical debate to an irresolvable value-based dispute (relativism). In this dissertation, I offer an intersubjective reading of van Fraassen. In doing so, I seek to extend what I think is an underdeveloped appeal to community in his work. Approaching van Fraassen with reference to community helps us to appreciate better his position (comprising his voluntarism and voluntarist epistemology, permissive rationality, and stance philosophy) and, as I hope to show, to respond to subjectivist and relativist concerns. In developing this community-based account, I first consider Brandom's model of reciprocal recognition. This gives us an understanding of stance choice as a process of mutually recognising and committing to particular values and attitudes. In choosing the empirical stance, say, I recognise and commit to the values of the empiricist community. In turn, this community recognises my commitment and acknowledges me as an empiricist, as an adherent of the empirical stance. In Brandom's model, then, we find an account of stance choice as a community matter rather than something purely subjective. This leaves the relativist issue unresolved: how can we defend our stance choice to another community, whose members perhaps do not share our relevant values? In addressing this, I consider Davidson's radical interpretation and his principle of charity. As Davidson shows us, if we want to interpret (and hence communicate with) another being, we must assume a shared background of agreement. Here I suggest that we might broaden this background agreement to include not only beliefs but also things like values and commitments. In this way, if I want to communicate with someone from another community, if I want to defend my values and stance choice to this being, then I must charitably assume that we share a common background of beliefs and values. At the very least, broadening the principle helps us to make further sense of van Fraassen's own response to Ho's relativist fears. Lastly I consider the epistemic issue of scientific and conceptual revolutions, in particular of the radical changes that are involved, in the context of community. I look at the role of emotion in van Fraassen's voluntarism and its connection to his notion of the "unfollowable rule". I suggest that further reflection on this connection might help us to make sense of drastic and emotional changes in perspective as a matter of community, since the unfollowable rule itself is community-based. As I hope to show, then, much light can be thrown upon van Fraassen The Empirical Stance by considering in detail the role of community and the theme of intersubjectivity in his work. This helps us to appreciate his position and offers him a genuine and detailed way to respond to the twin worries of subjectivism and relativism.